Acomodação dialetal de cariocas residentes em João Pessoa: uma análise sociolinguística - Oliveira, Lucas Possatti de (2020)
This work involving dialectal accommodation fits into the theoretical assumptions of the Communication Accommodation Theory (GILES et al., 1991) and the theoretical-methodological contributions of the Theory of Language Variation (LABOV, 1966, 2008 [1972]). It aims to observe and to analyze the dialectal accommodation of people born in Rio de Janeiro that are currently residing in the city of João Pessoa, from the investigation of the phenomenon of palatalization or non-palatalization of the coronal fricative /s/ in final coda position. The main variable phenomenon under study is the pronunciation of this fricative, which can be: in João Pessoa’s dialect, an alveolar pronunciation ([s], [z]); in Rio de Janeiro’s dialect, a palatal pronunciation ([ʃ], [Ʒ]). In this way, we aim to: a) verify if the non-palatalization convergence process occurs in the informants' speech; b) detect linguistic and extralinguistic variables that exert some form of pressure on accommodation; c) observe and describe the different linguistic attitudes of the speakers. The research corpus is composed of 16 informants from the city of Rio de Janeiro who have lived in the city of João Pessoa for at least 1 year and are at least 18 years old. These were stratified according to sex, age group and exposure time. The data were collected with the use of a digital recorder, and for quantitative analysis, they were coded and later analyzed with the aid of the statistical program Goldvarb X (SANKOFF, TAGLIAMONTE & SMITH, 2005). A qualitative analysis was subsequently made, based on data quantification, in order to observe the informants individually and comparatively. Based on the obtained results, we can conclude that the influence of the studied factors is clear, especially the factors of identity, linguistic attitudes, and exposure time, for the process of linguistic accommodation.